Celebrating Sabbath as a Holistic Health Practice: The Transformative Power of a Sanctuary in Time - Speedling, Barbara Baker (Journal of religion and health, 2019)
Sabbath-keeping has several holistic health benefits when done for intrinsic reasons. Most research on Sabbath-keeping is about individuals where Sabbath-keeping is customary. This organic inquiry describes how a Sabbath promoted transformation for ten women where Sabbath-keeping was not the norm. Six themes emerged: Sabbath-keeping enhanced self-awareness, improved self-care, enriched relationships, developed spirituality, positively affected the rest of a Sabbath-keeper's week, and Sabbath-keeping practices and philosophies also evolved over time. The author argues that reviving the best parts of Sabbath-keeping is an effective, accessible, holistic practice that can contribute to the well-being of individuals, communities, and the earth.